1997
DOI: 10.1016/s0006-3495(97)78267-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of individual alpha-helices of bacteriorhodopsin in dimyristol phosphatidylocholine. I. Structure and dynamics

Abstract: Understanding the role of the lipid bilayer in membrane protein structure and dynamics is needed for tertiary structure determination methods. However, the molecular details are not well understood. Molecular dynamics computer calculations can provide insight into these molecular details of protein:lipid interactions. This paper reports on 10 simulations of individual alpha-helices in explicit lipid bilayers. The 10 helices were selected from the bacteriorhodopsin structure as representative alpha-helical memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 78 publications
1
67
0
Order By: Relevance
“…[165,166]), MD simulations have been extended to increasingly complex membrane proteins [167][168][169][170]. These simulations are able to provide insights into the nature of the interactions between membrane proteins and their lipid environment [168,[171][172][173][174] and analysis of those crystal structures of membrane proteins that contain lipids provides a detailed structural per-spective on lipid/protein interactions [56,175]. A number of experimental studies have also revealed the importance of bound lipid molecules for the stability and function of some membrane proteins [176][177][178][179][180] For example, in the case of the K + channel KcsA, acidic phospholipids appear to bind to specific (non-annular) sites at which they play a role in refolding and possibly in function [181][182][183].…”
Section: Protein/lipid Interactionsmentioning
confidence: 99%
“…[165,166]), MD simulations have been extended to increasingly complex membrane proteins [167][168][169][170]. These simulations are able to provide insights into the nature of the interactions between membrane proteins and their lipid environment [168,[171][172][173][174] and analysis of those crystal structures of membrane proteins that contain lipids provides a detailed structural per-spective on lipid/protein interactions [56,175]. A number of experimental studies have also revealed the importance of bound lipid molecules for the stability and function of some membrane proteins [176][177][178][179][180] For example, in the case of the K + channel KcsA, acidic phospholipids appear to bind to specific (non-annular) sites at which they play a role in refolding and possibly in function [181][182][183].…”
Section: Protein/lipid Interactionsmentioning
confidence: 99%
“…Especially tryptophans and tyrosines are abundant in the interface, and they are generally thought to have an anchoring (4,5) and stabilizing (6,7) function. Moreover, it has been suggested that aromatic residues are essential for the proper folding and assembly (8), and functioning of integral membrane proteins (9,10).…”
mentioning
confidence: 99%
“…The NMR structure was obtained in solution and does not provide any information regarding lipid molecules around the peptide. Our method closely follows a previous method, which has been successfully applied to gramicidin, 18 alpha helical systems, 19,20 rhodopsin, 21 bacteriorhodopsin, 22 and fusion domain of influenza hemagglutinin (HA). 23 Constant membrane surface area is maintained, with constant normal pressure applied in the direction perpendicular to the membrane to adequately maintain constant surface tension of the lipid bilayer throughout the simulation.…”
Section: Methodsmentioning
confidence: 99%